Multiple Ligand-Bound States of a Phosphohexomutase Revealed by Principal Component Analysis of NMR Peak Shifts - Xu, Jia (Sci Rep, 2017)
Enzymes sample multiple conformations during their catalytic cycles. Chemical shifts from Nuclear Magnetic Resonance (NMR) are hypersensitive to conformational changes and ensembles in solution. Phosphomannomutase/phosphoglucomutase (PMM/PGM) is a ubiquitous four-domain enzyme that catalyzes phosphoryl transfer across phosphohexose substrates. We compared states the enzyme visits during its catalytic cycle. Collective responses of Pseudomonas PMM/PGM to phosphosugar substrates and inhibitor were assessed using NMR-detected titrations. Affinities were estimated from binding isotherms obtained by principal component analysis (PCA). Relationships among phosphosugar-enzyme associations emerge from PCA comparisons of the titrations. COordiNated Chemical Shifts bEhavior (CONCISE) analysis provides novel discrimination of three ligand-bound states of PMM/PGM harboring a mutation that suppresses activity. Enzyme phosphorylation and phosphosugar binding appear to drive the open dephosphorylated enzyme to the free phosphorylated state, and on toward ligand-closed states. Domain 4 appears central to collective responses to substrate and inhibitor binding. Hydrogen exchange reveals that binding of a substrate analogue enhances folding stability of the domains to a uniform level, establishing a globally unified structure. CONCISE and PCA of NMR spectra have discovered novel states of a well-studied enzyme and appear ready to discriminate other enzyme and ligand binding states.